Pomiar sprawności funkcjonowania controllingu w przedsiębiorstwie - Nowosielski, Krzysztof (Controllership functioning in an enterprise, 2006)
In the paper a general information about measuring of controlling functioning in an enterprise was presented. Main methods of this measurement, found by German specialists were shortly described. Hereinafter elaboration of the authors proposition of three main measures was pointed. Especially quality, efficiency and effectiveness gagers were presented with applicable patterns added.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 320-327